Effects of interface bonding properties on cyclic tensile behavior of unidirectional C/Si3N4 and SiC/Si3N4 composites. Issue 5 (24th March 2018) - Li, Longbiao; Reynaud, Pascal; Fantozzi, Gilbert
Abstract: In this paper, the effect of fiber/matrix interface bonding properties on the cyclic loading/unloading tensile stress−strain hysteresis loops of 2 different ceramic‐matrix composites (CMCs), ie, C/Si3 N4 and SiC/Si3 N4, has been investigated using micromechanical approach. The relationships between the damage mechanisms (ie, matrix multicracking saturation, fiber/matrix interface debonding and fibers failure), hysteresis dissipated energy and internal frictional damage parameter have been established. The damage evolution processes under cyclic loading/unloading tensile of C/Si3 N4 and SiC/Si3 N4 composites corresponding to different fiber/matrix interface bonding properties have been analyzed through damage models and interface frictional damage parameter. For the C/Si3 N4 composite with the weakest fiber/matrix interface bonding, the composite possesses the lowest tensile strength and the highest failure strain; the hysteresis dissipated energy increases at low peak stress, and the stress−strain hysteresis loops correspond to the interface partially and completely debonding. However, for the SiC/Si3 N4 composite with weak interface bonding, the composite possesses the highest tensile strength and intermediate failure strain; and the hysteresis dissipated energy increases faster and approaches to a higher value than that of composite with the strong interface bonding.